Prevalence of the uptake of Covid-19 vaccines: A cross-sectional study among the students of Bishop Stuart University in South-western Uganda. - Mary Jesenta Ngabirano; Francis Kazibwe; Ronald Bahati; Bright Laban Waswa; Wycliffe Tumwesigye (Student's Journal of Health Research, 2022)
Background:  Different studies have been carried out on acceptance of Covid-19 vaccines, willingness to be vaccinated against Covid-19, and factors associated with the uptake of Covid-19 vaccines but very few studies have been carried out to find out the prevalence of the uptake of Covid-19 vaccines, especially among university students. The aim of this study, therefore, is to find out the prevalence of the uptake of Covid-19 vaccines among the students of Bishop Stuart University.  Methodology:  A cross-sectional study design using qualitative and quantitative approaches was employed. Data was collected from a sample of randomly selected 370 respondents between 11th July and 3rd October 2022 from Bishop Stuart University. Qualitative and Quantitative data collection methods were employed. Statistical Package for Social Sciences version 26 was used during the analysis.  Results:  The prevalence of uptake of Covid-19 Vaccines among the students of BSU was 57.0% where the majority of the respondents were females, 52.2% (n=193), students aged ≤30 years, 59.2% (n=215), those from middle-income, 57.3% (n=212), Christians, 60.8% (n = 225) and undergraduates, 89.2% (n = 330). Conclusion:  More than half of the students of Bishop Stuart University were vaccinated with at least one of the vaccines against COVID-19 vaccine; the general uptake of Covid-19 vaccines among these students with a full dose was low as shown by the results of those who took a full dose of AstraZeneca, Johnson & Johnson or any other Covid-19 vaccine. Recommendation:  The study recommended that effective sensitization and psycho-education should be carried out to educate the general public about the effectiveness of the uptake of Covid-19 vaccines.